The Role of Students’ Perceptions of Assessment Tasks in Science Classes in Predicting Their Perception of the Classroom Assessment Environment - Abdulkadir Baygül; Serkan Buldur (Journal of Research in Mathematics, Science, and Technology Education, 2026)
Assessment practices shape how students experience learning, interpret classroom expectations, and respond to instructional processes. In science education, assessment tasks are especially important because they can direct students either toward learning-focused engagement or toward performance-based comparison. Against this background, the present study examined middle school students’ perceptions of classroom assessment environments and assessment tasks in science classes. It also investigated whether these perceptions varied according to gender and whether students’ views of assessment tasks predicted their perceptions of learning-oriented and performance-oriented assessment environments. The study was conducted using a correlational survey design. Participants were 2,277 students studying in Grades 6, 7, and 8 in the central district of a province in Türkiye. Data were gathered through the Perceptions of the Classroom Assessment Environment Scale and the Perceptions of Assessment Questionnaire. Descriptive statistics, dependent samples t-test, Friedman test, MANOVA, Pearson correlation analysis, and multiple regression analysis were used to analyze the data. The results indicated that students perceived their classroom assessment environment as more performance-oriented than learning-oriented. Perceptions of assessment tasks also varied significantly across dimensions; authenticity had the highest mean score, whereas congruence with planned learning had the lowest. Significant gender differences were observed in both the classroom assessment environment and assessment task perceptions, but the effect sizes were limited. Regression results showed that positive perceptions of assessment tasks predicted learning-oriented assessment environments positively and performance-oriented environments negatively. Overall, the findings indicate that assessment tasks designed to be meaningful, transparent, authentic, and responsive to students may support more learning-oriented assessment environments in science classes.